CdS quantum dot-sensitized solar cells based on nano-branched TiO(2) arrays - Liu, Chang (Springer, 2014)
Nano-branched rutile TiO(2) nanorod arrays were grown on F:SnO(2) conductive glass (FTO) by a facile, two-step wet chemical synthesis process at low temperature. The length of the nanobranches was tailored by controlling the growth time, after which CdS quantum dots were deposited on the nano-branched TiO(2) arrays using the successive ionic layer adsorption and reaction method to make a photoanode for quantum dot-sensitized solar cells (QDSCs). The photovoltaic properties of the CdS-sensitized nano-branched TiO(2) solar cells were studied systematically. A short-circuit current intensity of approximately 7 mA/cm(2) and a light-to-electricity conversion efficiency of 0.95% were recorded for cells based on optimized nano-branched TiO(2) arrays, indicating an increase of 138% compared to those based on unbranched TiO(2) nanorod arrays. The improved performance is attributed to a markedly enlarged surface area provided by the nanobranches and better electron conductivity in the one-dimensional, well-aligned TiO(2) nanorod trunks.